Concentration and competition in dual banking industry: a structural approach - Nafisah Mohammed,; Abdul Ghafar Ismail,; Junaina Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this paper is to investigate the evolution of market concentration and competition in Malaysian dual banking industry for the period of 1997-2013. This study utilized structural approach to investigate changes in the market structure particularly the level of concentration and competition that contributed by several structural changes which take place in the dual banking system. According to structural approach, concentration plays an important role in examining the link between concentration and competition. Therefore, present paper utilized the structural approach to measure various concentration indexes to provide significant evidence on the changes in the market structure of Malaysian banking industry for the largest available data set of 1997-2013. Pearson correlation analysis was also used to examine the consistency of those various measures used in this study. The paper found evidence that structural changes have altered the market structure of the banking industry which comprises of Islamic and conventional banking system. The results also indicate that dual banking industry operates in the monopolistic competition structure. Therefore, concentration indexes can be used by authorities to decide on the optimal number of banks operating in the industry.